Mutilating keratoderma with concomitant alopecia and keratoses follicularis spinulosa decalvans: X-linked olmsted syndrome and its response to isotretinoin - Gunjan Verma; Kabir Sardana; R K Gautam (Wolters Kluwer Medknow Publications, 2017)
We report a case of mutilating keratoderma with alopecia and keratoses follicularis spinulosa decalvans (KFSD), which was initially diagnosed as ectodermal dysplasia and Olmsted syndrome but was revisited as a case of X-linked Olmsted (XLO) syndrome. We focus on this uncommon entity (XLO) to highlight the differentials of alopecia with palmoplantar keratoderma.